Climate change mitigation opportunities based on carbon footprint estimates of dietary patterns in Peru - Vazquez-Rowe, I (2017)
The main objective is to analyze the environmental impacts of a set of 47 Peruvian food diet profiles, including geographical and socioeconomic scenarios. In order to do this, Life Cycle Assessment was used as the methodological framework to obtain the overall impacts of the components in the dietary patterns observed and primary data linked to the composition of diets were collected from the Peruvian National Institute for Statistics (INEI). Results were computed using the IPCC 2013 assessment method to estimate GHG emissions. No significant differences were observed between cities located in the three Peruvian natural regions.